Description of Nutritional Status, Hemoglobin Level and Tibc Level in Female Adolescents - Yuni Handayani; Ririn Handayani; Melati Puspita Sari; Ernawati Anggraeni (Jurnal Kesehatan dr. Soebandi, 2025)
Anemia is a public health problem that still has a high prevalence, especially among adolescents. According to WHO data, approximately 25% of adolescents worldwide experience anemia caused by iron deficiency. Adolescents are an age group that is vulnerable to anemia because they experience accelerated growth and menstruation, so they need nutritional intake containing iron. One of the challenges in treating anemia is identifying the right cause to determine iron deficiency. One of the laboratory examinations needed to establish an accurate diagnosis is TIBC (Total Iron Binding Capacity ), which measures the capacity of blood to bind iron through transferrin. This study aims to describe nutritional status, hemoglobin levels, and TIBC levels. This type of research is analytically descriptive. A cross-sectional observational research methodology is employed. 76 female adolescents from SMK Baitul Hikmah made up the study's population. Total sampling was the method employed, and it was based on the screening findings, which included female adolescents. The study's findings outline measurements of TIBC, hemoglobin, and BMI. There are 66.7% underweight adolescents, 9.5% have anemia, and 28.5% have abnormal TIBC levels. The study concluded that examining nutritional status, hemoglobin levels, and Total Iron Binding Capacity (TIBC) is important in assessing individuals' health, especially in malnutrition and anemia. Continuous monitoring and other examinations are needed to support the diagnosis of adolescents who experience anemia.